Selective Engagement of FcγRIV by a M2e-Specific Single Domain Antibody Construct Protects Against Influenza A Virus Infection - De Vlieger, Dorien; Hoffmann, Katja; Van Molle, Inge; Nerinckx, Wim; Van Hoecke, Lien; Ballegeer, Marlies; Creytens, Sarah; Remaut, Han; Hengel, Hartmut; Schepens, Bert; Saelens, Xavier (Frontiers in Immunology, 2019)
Lower respiratory tract infections, such as infections caused by influenza A viruses, are a constant threat for public health. Antivirals are indispensable to control disease caused by epidemic as well as pandemic influenza A. We developed a novel anti-influenza A virus approach based on an engineered single-domain antibody (VHH) construct that can selectively recruit innate immune cells to the sites of virus replication. This protective construct comprises two VHHs. One VHH binds with nanomolar affinity to the conserved influenza A matrix protein 2 (M2) ectodomain (M2e). Co-crystal structure analysis revealed that the complementarity determining regions 2 and 3 of this VHH embrace M2e. The second selected VHH specifically binds to the mouse Fcg Receptor IV (FcgRIV) and was genetically fused to the M2e-specific VHH, which resulted in a bi-specific VHH-based construct that could be efficiently expressed in Pichia pastoris. In the presence of M2 expressing or influenza A virus-infected target cells, this single domain antibody construct selectively activated the mouse FcgRIV. Moreover, intranasal delivery of this bispecific FcgRIV-engaging VHH construct protected wild type but not FcgRIV-/- mice against challenge with an H3N2 influenza virus. These results provide proof of concept that VHHs directed against a surface exposed viral antigen can be readily armed with effector functions that trigger protective antiviral activity beyond direct virus neutralization.